Causal relationship between gut microbiota and gynecological tumor: a two-sample Mendelian randomization study - Xiong, Yajun; Zhang, Xiaonan; Niu, Xiaoya; Zhang, Long; Sheng, Yanbing; Xu, Aiguo (Frontiers in Microbiology, 2024)
The causality between gut microbiota and gynecologic tumors remains unclear. This study employs Mendelian randomization (MR) to identify specific pathogenic bacterial communities associated with gynecologic tumors. We used data from the MiBioGen consortium on gut microbiota as the exposure. Uterine fibroids (UF), endometrial cancer (EC), ovarian cancer (OC), and cervical cancer (CC) were selected as outcomes. We investigated the causal relationship between gut microbiota and gynecologic tumors, conducted sensitivity analyses, and validated our findings in an independent cohort. Additionally, reverse MR explored the potential for reverse causation. We found a reduced risk of UF associated with higher Lachnospiraceae (OR: 0.882, 95% CI: 0.793-0.999, P = 0.982). Conversely, increased Lachnospiraceae was linked to a higher incidence of OC (OR: 1.329, 95% CI: 1.019-1.732, P= 0.036). This study established a causal connection between Lachnospiraceae and both UF and OC, providing new insights into the role of gut microbiota in gynecological tumors.